Polyarteritis Nodosa Presenting as Hypertensive Crisis (Bangladesh Critical Care Journal, 2021)
Hypertensive crisis is a deadly complication that should be avoided at all costs, let alone when it is associated with a rare disease, such as Polyarteritis Nodosa (PAN). We present a case of an adult female who initially came to Bangladesh Medical College Hospital (BMCH) with a prolonged high-grade fever responding to antipyretics. Upon follow up, the patient went into a hypertensive crisis, which led to the admission to Coronary Care Unit (CCU). The hypertension was difficult to control until the culprit was revealed. Polyarteritis Nodosa was then diagnosed by angiography, which showed tight stenosis of the left renal artery. Prompt treatment was initiated, and the patient's blood pressure normalized. Our case highlights the importance of detecting such diseases, since it may be easily missed as it usually presents with nonspecific symptoms. Newly detected Hypertension in patients of any age should not be taken lightly and should be investigated promptly. We hope our case report sheds enough light on this issue for other clinicians and researches to identify and prevent later on.Bangladesh Crit Care J March 2021; 9(1): 52-55